2017
DOI: 10.3390/nu9040361
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Iodine Deficiency in China: Achievements, Challenges and Global Implications

Abstract: The prevention of iodine deficiency through salt iodization has been recognized as a global success story, and China stands at the forefront of this achievement with one of the most successful programs in the world. High level political commitment, national mandatory legislation, a state-managed edible salt industry and a complex and highly sophisticated surveillance system have facilitated the success of the program. Challenges have arisen however, including: (i) concern that adequate iodine status in pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 44 publications
2
78
0
5
Order By: Relevance
“…Iodine deficiencies were prevalent in China until the introduction of universal salt iodization (USI) in 1995 . In 2000 and 2011, the USI standards were adjusted, and the principle of individualization of cities was proposed .…”
Section: Introductionmentioning
confidence: 99%
“…Iodine deficiencies were prevalent in China until the introduction of universal salt iodization (USI) in 1995 . In 2000 and 2011, the USI standards were adjusted, and the principle of individualization of cities was proposed .…”
Section: Introductionmentioning
confidence: 99%
“…27 Mainland China has led the way in sustaining the elimination of iodine deficiency through iodised salt since the early 1990s. 28 Nonetheless dietary iodine intake remains insufficient among pregnant women in Shanghai, Zhejiang, and other coastal cities where iodine is considered sufficient for the general population. 29,30 A national survey from the Mainland reported that the median UIC levels of pregnant and lactating women were 123-224 μg/L and 109-224 μg/L, respectively; median UIC was higher among those in inland cities, because of a higher iodine level in the salt and greater household coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Micronutrient interventions in China are presented in Table . Salt fortification with iodine has been a highly successful mandatory program since 1994 . It became fully regulated in 2011 under the State Council Order No.…”
Section: A Regional Approach To Combat Micronutrient Deficienciesmentioning
confidence: 99%
“…Salt fortification with iodine has been a highly successful mandatory program since 1994. 37 It became fully regulated in 2011 under the State Council Order No. 163 to prevent iodine deficiency disorders (IDDs), previously documented in the country.…”
Section: A Regional Approach To Combat Micronutrient Deficienciesmentioning
confidence: 99%